Pasie Lembang Village Tourism Planning Study Ecotourism-Based - Resky Rusnanda; Elby Sepriady; Asmaidi; Darma Setiawan Putra (Jurnal Inotera, 2022)
Pasie Lembang village is located in South Kluet District, which has excellent natural potential and community. In this village there are tourist attractions that are very important to be developed, including the Pasie Lembang beach tourist attraction where there is turtle breeding around it, but the problem that often occurs in tourism management is the absence of the right concept in its development so that it causes it not to develop properly the tourist attractions in the village. The problem at this time is the absence of proper tourism planning in the management of tourist attractions in Pasie Lembang Village. The methodology used in this study is the SWOT analysis method. The results of his research are that the concept of tourism planning in Pasie Lembang Village uses the concept of ecotourism. This concept focuses on aspects of nature conservation, aspects of social and economic empowerment of local communities, as well as aspects of learning and education. In developing this concept, a SWOT analysis has been carried out which resulted in 7 (seven) strategies – the strategies obtained are applied in tourism development planning in Pasie Lembang Village. The conclusions of this study are: 1) Pasie Lembang Village is located in South Kluet District, which is in accordance with the mandate of the RTRW of South Aceh Regency that the Pasie Lembang area is in a natural and artificial tourism allotment area. 2) Pasie Lembang Village is very suitable for tourism development with the concept of ecotourism which focuses on nature conservation.